2013
DOI: 10.1097/fpc.0b013e32835fcbb6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP3A4 and CYP3A5 polymorphisms on tacrolimus pharmacokinetics in Chinese adult renal transplant recipients

Abstract: This is the first study to extensively determine the effect of CYP3A4*1G and CYP3A5*3 genetic polymorphisms and hematocrit value on tacrolimus pharmacokinetics in Chinese renal transplant recipients. The findings suggest that CYP3A5*3 and CYP3A4*1G polymorphisms and hematocrit are determinant factors in the apparent clearance of tacrolimus. The initial dose design is mainly based on CYP3A5 and CYP3A4 genotypes as well as hematocrit. This result may also be useful for maintenance tacrolimus dose optimization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
119
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 23 publications
20
119
4
1
Order By: Relevance
“…No influence on the TAC logC0/D was observed for rs4646437 at different time points in CYP3A5 expressers. This is consistent with another study of CYP3A4 rs2242480 [41] . Actually, CYP3A4 rs2242480 is a functional SNP that could increase the activity of CYP3A4, and it resembles rs4646437 that can affect the hepatic CYP3A4 protein expression [19,42] .…”
Section: Discussionsupporting
confidence: 82%
“…No influence on the TAC logC0/D was observed for rs4646437 at different time points in CYP3A5 expressers. This is consistent with another study of CYP3A4 rs2242480 [41] . Actually, CYP3A4 rs2242480 is a functional SNP that could increase the activity of CYP3A4, and it resembles rs4646437 that can affect the hepatic CYP3A4 protein expression [19,42] .…”
Section: Discussionsupporting
confidence: 82%
“…Such results have been reported previously in the literature concerning this polymorphism. [5][6][7][8][9][10] A previous study by Patel and associates studied the effect of CYP3A5 polymorphism on tacrolimus drug dosing in North Indian renal allograft recipients. 11 To our knowledge, the present study is the first study to show the association between CYP3A5 genetic polymorphism and tacrolimus drug level in a South Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…Research in cases of renal, lung, and heart transplantation has confirmed that there is a strong correlation between cytochrome P450 (CYP) 3A5 gene polymorphism and patient-specific differences in responses to tacrolimus (Zheng et al, 2003(Zheng et al, , 2004Macphee et al, 2005;Li et al, 2007;Zuo et al, 2013). However, the situation is more complex in cases of liver transplantation.…”
Section: Introductionmentioning
confidence: 96%